2020
DOI: 10.3389/fcell.2020.00565
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning Lidocaine as an Anticancer Drug: The Role Beyond Anesthesia

Abstract: While cancer treatment has improved dramatically, it has also encountered many critical challenges, such as disease recurrence, metastasis, and drug resistance, making new drugs with novel mechanisms an urgent clinical need. The term “drug repositioning,” also known as old drugs for new uses, has emerged as one practical strategy to develop new anticancer drugs. Anesthetics have been widely used in surgical procedures to reduce the excruciating pain. Lidocaine, one of the most-used local anesthetics in clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 130 publications
0
26
0
Order By: Relevance
“…Lidocaine is a local anesthetic used for relieving neuropathic pain, regional pain, and hyperalgesia in clinical therapy [ 6 ]. In recent years, lidocaine has been used as an anticancer drug in cancer treatment [ 7 ]. Sui et al reported that lidocaine inhibited cell metastasis in gastric cancer by upregulating miR-145 to activate the NF-κB signaling pathway [ 8 ], and Sun and Sun found that lidocaine retarded lung cancer progression by regulating the miR-539/EGFR axis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lidocaine is a local anesthetic used for relieving neuropathic pain, regional pain, and hyperalgesia in clinical therapy [ 6 ]. In recent years, lidocaine has been used as an anticancer drug in cancer treatment [ 7 ]. Sui et al reported that lidocaine inhibited cell metastasis in gastric cancer by upregulating miR-145 to activate the NF-κB signaling pathway [ 8 ], and Sun and Sun found that lidocaine retarded lung cancer progression by regulating the miR-539/EGFR axis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This will confirm the significance of anesthetics for cancer patients and guide clinical practice. Local anesthetics can reach the circulatory system via absorption from the injection site or direct intravenous injection (e.g., lidocaine) to affect the circulating tumor cells released from the primary tumor during surgery [38]. Amide local anesthetics act on nerve cells by blocking voltage-gated sodium channels, resulting in decreased depolarization and repolarization rates of excitatory nerve cell membranes [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…Lidocaine is widely used as a local anesthetic. In addition to having anesthetic effects, lidocaine has also been reported to have inhibitory effects on tumors (25)(26)(27). A previous study demonstrated that lidocaine can inhibit vascular endothelial growth factor-A-induced angiogenesis, and therefore may be able to suppress cancer progression (28).…”
Section: Discussionmentioning
confidence: 99%